Neue Klasse von Methyltransferasen mit Zyklisierungsaktivität - Birgit Piechulla; Nancy Magnus; Marie Chantal Lemfack; Stephan Von Reuss (BIOspektrum, 2021)
Microorganisms release small volatile metabolites with unique structures, e. g. the polymethylated homosesquiterpene sodorifen from Serratia plymuthica . Two unusual enzymes with novel features are involved in its biosynthesis, a C -methyltransferase with cyclization activity and a terpene synthase that accepts a non-canonical monocyclic C 16 substrate. The novel class of methyltransferases represents an alternative route that enlarges terpene diversity.